Konsep Tuhan dalam Perspektif Ibnu Sina dan Mulla Shadra - Arif Rahman Hakim (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the concept of God in the perspective of Ibn Sina and Mulla Sadra. This study uses a qualitative method that applies the literature study method. The formal object of this research is the views of Ibn Sina and Mulla Sadra. While the material object is the concept of God. The results and discussion show that Ibn Sina used the obligatory concept of al-Wujud in explaining God, while Mulla Sadra used wahdah al-Wujud. In conclusion, there are similarities and differences in the thoughts of Ibn Sina and Mulla Sadra. Both believe that God is a necessary form. In thinking about the universe as God's creation, Mulla Sadra divided God's creation into two, the macrocosm (universe) and the microcosm (humans), while Ibn Sina did not divide it, but called it mumkin al-Wujud.